Sunscreen: Assessing Knowledge and Attitudes Towards Sunscreen Usage Among Students for Skin Cancer Prevention - Arya, Muhammad Imam; Jusuf, Mutiara Nabilla; Utami, Fitri (Newinera Publisher, 2024)
Sunlight contains Ultraviolet Radiation (UVR) which can damage the skin layer and become a risk factor for skin cancer. The increase of ultraviolet index in Indonesia and the incidence of skin cancer encourages the use of sunscreen to maintain skin health. This study aims to determine the level of knowledge and attitude categories related to the use of sunscreen in students at SMA Negeri 2 Padalarang in 2023 as an effort to prevent skin cancer. This research is a descriptive categorical non-experimental quantitative approach with a cross sectional study design. The data collection technique used a questionnaire containing 18 knowledge measurement items and 12 attitude measurement items. Results of the 286 respondents only 11.19% of respondents had knowledge in the good category, 44.06% of respondents were in the sufficient category, and respondents who had a poor level of knowledge were 44.76% of respondents. The use of sunscreen in 286 respondents showed that 64.34% of respondents had a positive attitude, while 35.66% of respondents had a negative attitude in using sunscreen. The majority of respondents have insufficient knowledge about sunscreen as a prevention of skin cancer. Although the average attitude towards using sunscreen is positive, the main reason for using it is to prevent sunburn, dark spots, and facial aesthetics, not specifically for skin cancer prevention.